Evaluation of hydrologic impact of an irrigation curtailment program using Landsat satellite data - Velpuri, Naga Manohar; Senay, Gabriel B.; Schauer, M.; Garcia, C. A.; Singh, R.K.; Friedrichs, M.; Kagone, S.; Haynes, J.; Conlon, T. (Wiley, 2020)
Upper Klamath Lake (UKL) is the source of the Klamath River that flows through southern Oregon and northern California. The UKL Basin provides water for 81,000+ ha (200,000+ acres) of irrigation on the U.S. Bureau of Reclamation Klamath Project located downstream of the UKL Basin. Irrigated agriculture also occurs along the tributaries to UKL. During 2013–2016, water rights calls resulted in various levels of curtailment of irrigation diversions from the tributaries to UKL. However, information on the extent of curtailment, how much irrigation water was saved, and its impact on the UKL is unknown. In this study, we combined Landsat-based actual evapotranspiration (ETa) data obtained from the Operational Simplified Surface Energy Balance model with gridded precipitation and U.S. Geological Survey station discharge data to evaluate the hydrologic impact of the curtailment program. Analysis was performed for 2004, 2006, 2008–2010 (base years), and 2013–2016 (target years) over irrigated areas above UKL. Our results indicate that the savings from the curtailment program over the June to September time period were highest during 2013 and declined in each of the following years. The total on-field water savings was approximately 60 hm3 in 2013 and 2014, 44 hm3 in 2015, and 32 hm3 in 2016 (1 hm3 = 10,000 m3 or 810.7 ac-ft). The instream water flow changes or extra water available were 92, 68, 45, and 26 hm3, respectively, for 2013, 2014, 2015, and 2016. Highest water savings came from pasture and wetlands. Alfalfa showed the most decline in water use among grain crops. The resulting extra water available from the curtailment contributed to a maximum of 19% of the lake inflows and 50% of the lake volume. The Landsat-based ETa and other remote sensing datasets used in this study can be used to monitor crop water use at the irrigation district scale and to quantify water savings as a result of land-water management changes.